Pencegahan Dan Penanganan Alternative Terapi Pada Anak Yang Mengalami Kekerasan Seksual - Dwi Yuniarahmah; Atikah Rizky Amalia; Arindra Dwi Angraini; Anisa Noviana Herlambang; Anggi Indah Partiwi; Ade Nabila Rosda H; Adela Dwi Rizki D; Elsi Sopiyatul Fuadah; Fatmawati; Indana Zulva Nikmah; Indah Ambarwati Iraningrum; Ameliana Safitri; Darmawan Wibisana; Dianatika Azmi; Jelytha Renova Siringoringo; Renta Sianturi (AKPER Pasar Rebo, 2022)
Abstract Sexual violence against children is a crime that must be overcome and is a deviant activity carried out forcibly by adults on children. The impact of sexual violence affects the development of children both physically and mentally. Sexual crimes can cause problems with pregnancy in children and sexually transmitted diseases in the form of reproductive disorders. Writing methods using databases and search websites include Google Scholar, PubMed, Science Direct, SAGE, Semantic Scholar, PlosOne, ProQuest, Taylor & Francis. In the search for articles, the keywords “Therapy”, “Nursing Therapy”, “Nursing Interventions”, “Child victims”, “Children sexual abuse”, “Sexual abuse” and “rape with the specified inclusion criteria, are articles on the topic of violence prevention. sexual abuse in children with counseling, articles on the topic of therapy or interventions in the treatment of children with sexual violence. articles in English and Indonesian. The purpose of providing play interventions, drawing therapy, providing sexual health education so that children and parents know the importance of sexual knowledge which is violence against children physically and mentally. From the actions that have been taken, the results have proven effective in dealing with and preventing trauma due to sexual violence in children, so it is hoped that these interventions can be used in mental health services and can increase knowledge, attitudes, positive behavior of children and families in preventing and dealing with trauma due to sexual violence in children.